Punch planting - Scheidtweiler, Thomas W.; Eikel, Gottfried (agricultural engineering.eu, 2001)
Minimum tillage is the standard procedure in systems using hand labour or animal traction rather than any special soil-conserving measure. Due to the limited power output of this mechanization level,tillage leaves rough soil surfaces with imperfectly incorporated plant residues. This is good for soil conservation, but most conventional planters are not able to cope with such surface conditions. Therefore, the animal-drawn moldboard plow is often not just the first, but also the only link in the mechanization chain.